2022
DOI: 10.1002/aoc.6569
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical assessment of Alzheimer's disease using novel designed 99mTc‐labeled RGD‐based pro‐apoptotic cyclic peptide as a promising SPECT agent

Abstract: The increased prevalence of neurodegenerative disorders such as Alzheimer's disease, Parkinson's disease, and glioma results in increased risks to abolish the healthy life. This is because of inducing alternation causes into the intracellular compartment as well as noncell compartments. Therefore, herein, a simple and facile radiosynthesis strategy was employed for the development of a novel 99mTc (t1/2 = 6 h, Er = 140 keV) labeled diethylenetriamine pentaacetic acid (DTPA) conjugated cyclic heptapeptide (99mT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Hence, the tumor inhibitory abilities of PDC were significantly improved compared with PTX alone, which highlighted the considerable antitumor efficacy with an increased order of anticancer activity as PDC > PTX > CPP. Further, it can be seen from Figure 7a−c that c[RGDKLAK] being a potent cell-targeting 27 and cell-penetrating peptide 49 itself shows limited anticancer activity, which is comparatively smaller than that of free PTX and our designed PDC. This small anticancer effect of this dual-targeting peptide sequence is because of the proapoptotic KLA tri motif, which specifically targets the cancer cell mitochondria and disrupts its membrane potential to induce apoptosis via the intrinsic pathway as reported previously.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the tumor inhibitory abilities of PDC were significantly improved compared with PTX alone, which highlighted the considerable antitumor efficacy with an increased order of anticancer activity as PDC > PTX > CPP. Further, it can be seen from Figure 7a−c that c[RGDKLAK] being a potent cell-targeting 27 and cell-penetrating peptide 49 itself shows limited anticancer activity, which is comparatively smaller than that of free PTX and our designed PDC. This small anticancer effect of this dual-targeting peptide sequence is because of the proapoptotic KLA tri motif, which specifically targets the cancer cell mitochondria and disrupts its membrane potential to induce apoptosis via the intrinsic pathway as reported previously.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For in vivo tumor-model studies, technetium-99mlabeled diethylenetriamine pentaacetic acid ( 99m Tc-DTPA) was conjugated with the ε-amino group of a terminal lysine residue of the peptide by a simple condensation reaction as a protocol reported in the literature. 49 Briefly, cDTPA (0.061 g, 0.17 mmol, 1.13 equiv) in 150 μL of DMSO and HATU (0.064 g, 0.17 mmol, 1.13 equiv) in 150 μL of DMF were mixed and stirred for 20 min at room temperature. The white crystals of PDC (0.255 g, 0.15 mmol, 1.0 equiv) were dissolved in Milli-Q water (600 μL), added dropwise to the cDTPA mixture, and stirred for another 30 min at room temperature.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the same group synthesized a novel radiotracer ( 99m Tc-DTPA-c­[RGDKLAK]) and studied its efficacy to diagnose Alzheimer’s disease preclinically. The results showed that radiotracer was highly accumulated in α v β 3 -integrin expressing brain region with decreased uptake in the liver and kidneys having target-to-nontarget ratio 28.47 ± 2.53 at 3 h postinjection . Moreover, Rizvi et al for the first time reported the synthesis of synergistic cell-penetrating peptide (cRGD-KLAK) conjugated with paclitaxel via ester linkage with succinic acid as cleavable linker.…”
Section: Peptides For Delivery Cargoes Through Bbbmentioning
confidence: 99%
“…The results showed that radiotracer was highly accumulated in α v β 3integrin expressing brain region with decreased uptake in the liver and kidneys having target-to-nontarget ratio 28.47 ± 2.53 at 3 h postinjection. 152 Moreover, Rizvi et al for the first time reported the synthesis of synergistic cell-penetrating peptide (cRGD-KLAK) conjugated with paclitaxel via ester linkage with succinic acid as cleavable linker. The proposed PDC was observed to possess improved solubility in water, enhanced stability in blood circulatory system (≥90%), as well as promising tumor-growth inhibitory effect (2.82−3.24-folds) in glioblastoma models.…”
Section: ■ Peptides For Drug Delivery Systemmentioning
confidence: 99%